2021
DOI: 10.1002/pssa.202000690
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Coated Gold Chips for Enhanced Goos–Hanchen Shift Plasmonic Sensing

Abstract: Plasmon‐based sensing relies on the interaction of photons with nanostructured materials. Surface plasmon resonance (SPR) biological and chemical sensors offer unique advantages of real‐time and label‐free detection techniques and therefore, they have been around in the commercial market for many decades. The principle of the Goos–Hanchen (GH) shift, whereby linearly polarized light undergoes a small lateral shift upon total internal reflection at a dielectric surface, is highly sensitive to refractive index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…GH shift sensing methodology is employed to evaluate the sensitivity enhancement of graphene‐coated Au chips. [ 133 ] A customized setup was used that consisted of a laser source, a polarizer, the sensing chip attached to the prism, and a position detector. Briefly, the change in GH shift was calculated by measuring the difference in the x coordinate of the p‐polarized reflected light for de‐ionized (D.I.)…”
Section: Review Of Recent Plasmonic Sensing Workmentioning
confidence: 99%
“…GH shift sensing methodology is employed to evaluate the sensitivity enhancement of graphene‐coated Au chips. [ 133 ] A customized setup was used that consisted of a laser source, a polarizer, the sensing chip attached to the prism, and a position detector. Briefly, the change in GH shift was calculated by measuring the difference in the x coordinate of the p‐polarized reflected light for de‐ionized (D.I.)…”
Section: Review Of Recent Plasmonic Sensing Workmentioning
confidence: 99%
“…It has also been shown that the sensitivity of bimetallic sensors based on the graphene-hexagonal boron nitride heterostructure can be enhanced by increasing the GHS in the infrared band [7]. Likewise, giant GHS has been predicted theoretically [8][9][10][11] and demonstrated experimentally [12][13][14][15]. In a recent experiment, Sreekanth et al demonstrated a thirtyfold enhancement in GHS at the Brewster angle of a nanophotonic cavity operating at a given wavelength [12].…”
Section: Introductionmentioning
confidence: 98%
“…Figure 10.3 Optics experiment instruments and setup for the GH shift estimation of the Au and Au + graphene based SPR sensors 130. reflected light to the change in R.I. of the analyte layer.…”
mentioning
confidence: 99%
“…reflected light to the change in R.I. of the analyte layer. For the bio-molecular sensing experiment, the experiment procedure remains the same except that we use Phosphate buffered saline (PBS) buffer and 0.25 mg/mL BSA in PBS as the analyte for the first and second sets respectively 130. GHp(Theta)=x_positionp(Theta)|0.1%glycerol-x_positionp(Theta)|D.I.…”
mentioning
confidence: 99%
See 1 more Smart Citation